Performance evaluation of various growing media in vertical green wall for greywater treatment in hyper-arid climate - Jasir Jawad (17191468) (2025)
Water scarcity in hyper-arid regions like the Middle East demands sustainable solutions to reduce reliance on energy-intensive desalinated water. Greywater presents a viable alternative for non-potable uses such as irrigation and toilet flushing. This work investigates the effectiveness of an outdoor vertical green wall system for treating greywater using three media combinations: (i) conventional soil and peat moss mix, (ii) coco coir-based mix, and (iii) charcoal-based mix. Through a specifically designed case study, the system was tested in Qatar’s hyper-arid climate using untreated greywater from sinks, showers, and laundry at a student hostel. Key parameters analyzed include the physical properties of the media, effluent water quality (pH, conductivity, turbidity, organic content, nitrogen, and nutrients), and plant health, assessed through chlorophyll content and the normalized difference vegetation index (NDVI) using hyperspectral imaging. Soil and coco coir-based media effectively reduced conductivity and potassium levels up to 40 % and 92 %, respectively, but caused organic matter leaching, increasing organic content in the effluent. In contrast, the charcoal-based media achieved the highest removal efficiency for turbidity (97 %) and ammonium (90 %), improving the effluent water quality while maintaining organic levels similar to the feed. The contaminants such as caffeine (99 %) and diethyltoluamide (DEET) (81.2 %) were more effectively removed by charcoal, while soil and coco coir-based media showed better performance for Acetaminophen (up to 99 %). These variations suggested that a blended media approach could optimize contaminant removal. Addressing economic and operational challenges is equally important to enhance performance and ensure cost-effectiveness and operational reliability in greywater treatment. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.119792